Africa100 - Samii, Madjid (JOURNAL OF GLOBAL NEUROSURGERY, 2021)
Neurosurgery made a fascinating advancement in the last century. However, its historical development was somewhat slower than that of other surgical specialties due to the complexity of the central nervous system. Initial attempts to treat brain disease surgically have been related to high morbidity and mortality. Only the better understanding of brain structure and function localization and the introduction of antisepsis, anesthesia, and hemostasis at the end of the 19th century led to increased interest and rapid advancement in the field. The other development of neurosurgery was distributing the acquired knowledge and making this highly specialized care available to all patients around the world. Among all other surgical disciplines, global neurosurgery was the foundation of neurosurgical organizations around the world, and their close cooperation, few countries founded the WFNS in 1955. The first president was Jefferson, and the first WFNS congress was held in 1957 in Brussels (congress president professor A. Walder). WFNS initiated a world congress every four years to gather neurosurgeons for scientific exchange.